Effects of Graphene Oxide on the Structure and Properties of Regenerated Wool Keratin Films - Li, Bo (Polymers (Basel), 2018)
Much research has focused on improvement of the structural and mechanical properties of regenerated keratin materials by physical or chemical methods in recent years. In this research, regenerated keratin materials were modified with graphene oxide (GO). The properties of modified keratin films and the mechanism of interaction between GO and keratin macromolecules were studied. The SEM and XRD test results showed that the orientation of keratin macromolecules could be effectively improved by GO, which favored improvement of the keratin material’s crystallinity and made the films more uniform and compact. The thermal stability and mechanical properties of GO-modified keratin films were also improved significantly. At the same time, the reaction mechanism between keratin and GO materials was analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), FT-IR, and Raman spectroscopy. It was shown that there was no chemical reaction between GO and keratin molecules, and the interaction between them was mainly via hydrogen bonding and van der Waals forces.